1989
DOI: 10.1038/337576a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a retroviral protease proves relationship to aspartic protease family

Abstract: Retroviral gag, pol and env gene products are translated as precursor polyproteins, which are cleaved by virus-encoded proteases to produce the mature proteins found in virions. On the basis of the conserved Asp-Thr/Ser-Gly sequence at the putative protease active sites, and other biochemical evidence, retroviral proteases have been predicted to be in the family of pepsin-like aspartic proteases. It has been suggested that aspartic proteases evolved from a smaller, dimeric ancestral protein, and a recent model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
175
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(179 citation statements)
references
References 23 publications
4
175
0
Order By: Relevance
“…These hydrogen bonds are, most likely, responsible for the low pK a values of the active-site aspartic acid residues (59,60). Aspartic proteases from retroviruses and some plant viruses are related to the eukaryotic aspartic proteases, but the active protease is a homodimer, the active site(s) of which contain the conserved Asp-Thr/Ser-Gly motif (61,62). In contrast to the eukaryotic aspartic proteases, conserved Ser or Thr residues are absent from the ϩ3 position relative to the active site Asp residue of retroviral aspartic proteases.…”
Section: Discussionmentioning
confidence: 99%
“…These hydrogen bonds are, most likely, responsible for the low pK a values of the active-site aspartic acid residues (59,60). Aspartic proteases from retroviruses and some plant viruses are related to the eukaryotic aspartic proteases, but the active protease is a homodimer, the active site(s) of which contain the conserved Asp-Thr/Ser-Gly motif (61,62). In contrast to the eukaryotic aspartic proteases, conserved Ser or Thr residues are absent from the ϩ3 position relative to the active site Asp residue of retroviral aspartic proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Aspartic proteinases are usually divided into the following groups : pepsins and chymosins, cathepsins, renins, fungal aspartic proteinases and retroviral aspartic proteinases [3]. Eucaryotic aspartic proteinases are usually bilobal, monomeric molecules, while retroviral proteinases are functional as dimers of identical polypeptides [4]. Available evidence suggests that all eucaryotic aspartic proteinases are synthesized as zymogens.…”
Section: Introductionmentioning
confidence: 99%
“…This work has the ultimate objective of understanding the structure of the enzyme and interactions with its substrate in sufficient detail to allow rational design of specific inhibitors and antiviral agents. Miller et al (1989a) reported a structure for the proteinase of Rous sarcoma virus (RSV); both Navia et al (1989) and Lapatto et al (1989) reported structures for HIV-1 proteinase; and Wlodawer et al (1989) reported a structure for a synthetic HIV-1 proteinase (in which the cysteine residues were replaced by c~-amino-n-butyrate). The material for these analyses was obtained by three methods: the RSV enzyme was extracted from virions; Navia et al and Lapatto et al utilized Various, studies, including the crystallographic analyses, indicate that the active form of the proteinase is a dimer (see also, for instance, Meek et al, 1989).…”
Section: Retroviral Proteinasesmentioning
confidence: 99%